Comparative Susceptibility of Different Populations of Amblyomma sculptum to Rickettsia rickettsii - Gerardi, Monize; Ramírez-Hernández, Alejandro; Binder, Lina C.; Krawczak, Felipe S.; Gregori, Fábio; Labruna, Marcelo B. (Frontiers in Physiology, 2019)
The bacterium Rickettsia rickettsii is the etiological agent of Brazilian spotted fever (BSF), which is transmitted in Brazil mainly by the tick Amblyomma sculptum. Herein, larvae and nymphs of six populations of A. sculptum were exposed to R. rickettsii by feeding on needle-inoculated guinea pigs, and thereafter reared on uninfected guinea pigs or rabbits. Two tick populations were exposed to autochthone R. rickettsii strains, whereas four tick populations were exposed to non- autochthone strains. The six geographically different populations of A. sculptum showed different susceptibilities to R. rickettsii, higher among the two tick populations that were exposed to their autochthone R. rickettsii strain. In addition, higher rates of transovarial transmission of R. rickettsii and vector competence success also included the two tick populations that were exposed to autochthone R. rickettsii strains. These results indicate that the susceptibility of A. sculptum to R. rickettsii varies among different tick populations, with a clear bias for higher susceptibility to an autochthone R. rickettsii strain that has already coevolved with a the tick population for some time. Our results demonstrated that the R. rickettsii infection induces higher mortality of engorged larvae and nymphs, and tend to reduce the reproductive fitness of engorged females. All together, these results might explain the low R. rickettsii-infection rates of A. sculptum under natural conditions (usually <1%), and indicate that an A. sculptum population should not be able to sustain a R. rickettsii infection for successive tick generations without the creation of new cohorts of infected ticks via horizontal transmission on vertebrate rickettsemic hosts (amplifying hosts). Finally, despite of the ubiquitous distribution of A. sculptum in southeastern and central-western Brazil, most of the populations of this tick species are devoid of R. rickettsii infection. This scenario might be related to two major factors: (i) insufficient numbers of susceptible amplifying hosts; and (ii) lower susceptibilities of many tick populations. While the first factor has been demonstrated by mathematical models in previous studies, the second is highlighted by the results observed in the present study.